Macroeconomics, agriculture, and food security: A guide to policy analysis in developing countries - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2015)
Why write a book on macroeconomic policies and their links to agriculture and food security in developing countries? The food price spikes of the years just prior to 2010 and the economic, political, and social dislocations they generated refocused the attention of policymakers and development practitioners on the agricultural sector and food security concerns. But even without those traumatic events, the importance of agriculture for developing countries—and for an adequate functioning of the world economy— cannot be denied. First, although declining over time, primary agriculture still represents important percentages of developing countries’ overall domestic production, exports, and employment. If agroindustrial, transportation, commercial, and other related activities are also counted, then the economic and social importance of agriculture-based sectors increases significantly. Furthermore, large numbers of the world’s poor still live in rural areas and work in agriculture. Through the links via production, trade, employment, and prices, agricultural production is also crucial for national food security. Second, it has been shown that agriculture in developing countries has important growth and employment multipliers for the rest of the economy, and agriculture seems to have larger positive effects in reducing poverty than growth in other sectors. Third, agriculture is not only important for individual developing countries, but it has global significance, considering the large presence of developing countries in world agricultural production and the increasing participation in international trade of those products (these three points will be covered in greater detail in Chapter 1).